Effect of Monetary Policy of the People’s Bank of China on Stock Market Returns - Kažytė, Agnė; Valukonis, Mantas (Jaunųjų mokslininkų darbai, 2017)
The relationship between the interest rate and the stock market most often is negative and statistically significant in developed countries. However, this relationship can be affected not only by various monetary policy instruments, the prevailing sentiments in the market or other factors but also by different development levels Seeking to find out whether China’s stock market positively reacts to expantionary policy and negatively to contarctionary policy the author of the paper analyzed the period 2007-2016 using the event study as a research method. Research findings showed that when the interest rate is raised and the required reserve ratio is reduced China’s stock market does not react as a developed market. However, when the interest rate is reduced and the required reserve ratio is raised China’s stock market reacts as a developed market.
Keywords: The People's Bank of China; Monetary Policy; China’s Stock Market